Revamped fly‐over for accurate colon visualisation in virtual colonoscopy. Issue 4 (1st August 2015) - Ismail, Marwa; Elshzaly, Salwa; Farag, Aly; Sites, Chuck; Curtin, Robert; Falk, Robert; Seow, Albert; Dryden, Gerald
Abstract : This study revisits a visualisation technique for virtual colonoscopy, known as virtual fly‐over (FO). The method views the entire colon anatomy from above the centreline. It assigns two cameras located on opposite sides of the centreline, each of which is responsible for viewing one half of the colon. This approach has several advantages over related colon visualisation methods with regards to visibility coverage and polyp detection rate. However, the traditional FO implementation created a few drawbacks that hinder complete visualisation. For example, it could overlook polyps located on the line between the two halves, and it has no data‐specific initialisation for cutting planes. The authors enhance the FO method in a number of respects in this study: resolve the cutting issue and improve the virtual camera setup in order to better visualise both the colon surface's hidden structures and polyps that are difficult to locate. Quantitative validation of the revamped FO on 30 actual clinical datasets with complicated shapes and large volumes demonstrated that the average surface visualisation rate is equal to 99.5 ± 0.2%. Also, true and synthetic polyps with various shapes and sizes were used to clinically validate the proposed method. Detection rate is up to 100% on the tested sets.